Ondel-ondel galau : let's talk about Betawi culture (PT. Gramedia Pustaka Utama, 2018)
Ondel-ondel Galau is about a young girl, Vina, who has been living a typical middle school life: going to school in the morning and heading back home in the afternoon. Worn out by the same cycle every day, Vina took on a new challenge and joined her school?s traditional Betawi music club, where she plays the violin. With this new activity, she makes new friends, faces new challenges and exposing herself to her own native culture that she has never known before.